Amazing animal disguises - Weber;Belinda (London Kingfisher Books, 2002)
It is a children's book that explores the fascinating world of animal camouflage and mimicry. In this engaging and educational book, readers are introduced to a variety of animals that use disguise as a survival strategy in the wild.